Study of maternal mortality in a tertiary care hospital in a tribal KBK area of Odisha, India - Behuria, Sasmita; Puhan, Jyoti Narayan; Ghosh, Subhra; Nayak, Bhabani Sankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pregnancy, although being considered a physiological state, carries risk of serious maternal morbidity and at times death. This is due to various complications that may occur during pregnancy, labor, or thereafter. The major causes of maternal mortality are mostly preventable through regular antenatal check-up, proper diagnosis, and management of labor complications. Therefore, the factors at different levels affecting the use of these services need to be clearly understood. The aim is to study the incidence of MMR, assess the epidemiological aspects, causes of maternal mortality and avoidable factors that can prevent maternal deaths. Methods: A retrospective hospital-based study was conducted in obstetrics and gynecology department, SLN MCH, a tertiary care referral hospital in a tribal area of southern Odisha over a period of 2 years from April 2017 to March 2019. Results: A total of 108 deaths were analyzed over 2 years period and MMR was calculated to be 1124/1 lakh live births. Most of the maternal deaths occurred in the age group of 20-24 years (35.1%), majority of maternal deaths were observed in multipara (46.3%), 70.3% deaths occurred within 24 hours of admission. Hypertensive disorders in pregnancy (37%) were the leading direct cause followed by hemorrhage (14.8%) and sepsis (11.1%). Among the indirect causes jaundice (7.4%) and anaemia (3.7%) were the leading cause. Conclusions: MMR in our study was very high as compared to national average of 167/1,00,000 live births, being a tertiary care hospital as most of the patients were referred from peripheral centers. Most maternal deaths are preventable by intensive health education, basic obstetric care for all, strengthening referral and communication system and emphasizing on overall safe motherhood.